Intersected Paths of People and Raw Materials: Mobility between Puna and Valleys of the Northwest of Argentina during the Middle Holocene - Martinez, Jorge Gabriel (2020)
The comparative study of archaeological evidences belonging to two differentiated geographical areas within northwestern Argentina is addressed in this paper: Antofagasta de la Sierra in the southern Puna (Catamarca) and Quebrada de Los Corrales located in a sector of intermontane valleys (northwest of Tucumán). Both areas have long-term occupational sequences within the Holocene, where we have been able to identify the presence of rocks and other materialities that together show a clear interaction among human groups that incorporated these environments into their patterns of mobility and use of space since the beginning of the Holocene. The record in Antofagasta de la Sierra of vegetal raw materials for the preparation of weapon systems for hunting from Valleys and Yungas from ca.9800 years BP, denotes an early dependence of the hunter-gatherers groups of the Puna on critical resources of allochthonous origin. As a counterpart, the recent identifcation of obsidians of Puna origin in the Quebrada de Los Corrales from ca.7420 years BP, allows us to confrm an early bidirectional East-West fow of people and objects between the southern Puna and the Eastern Valleys, which opens a interesting social and technological spectrum to be explored in terms of mobility and interaction that explains the trajectory of said evidences.